The economics of sport - Sandy, R.; Sloane, P.; Rosentraub, M. (Macmillan Publishers Limited, 2004)
This text, by three distinguished authors, applies the theories and techniques of economic analysis to sport and topics related to the business of sport. It builds on a basis of introductory microeconomics and continues the discussion, generally at an intermediate standard. The text has an international perspective, primarily the US, Canada, Europe and Australia, and contains relevant and entertaining case studies. The text suits both undergradute and postgraduate students in that while it provides a clear progression of topics throughout, it also incorporates optional sections in each chapters of a higher and more challenging level. Club and League Objectives: Profit Versus Utility Maximisation Demand and Pricing The Labor Market for Players Discrimination in Professional Sports The Economic Implications of Sports Broadcasting Sports Teams and Leagues: From A Business Necessity to Dominating Cartels Sports and Economic Development Financing the Facilities Used by Professional Sports Teams Non-Team Sports and Incentives College Sports Government and Sports Policy